Complete formalization of taxa with their names, contents and descriptions improves taxonomic databases and access to the taxonomic knowledge they support. Issue 7 (3rd October 2021) - Bourgoin, Thierry; Bailly, Nicolas; Zaragueta, René; Vignes-Lebbe, Régine
Abstract : As concepts, taxa should be addressed through their name, their description (definition by intension) or their content (definition by extension). Each part of this taxonomic triplet is necessary but none alone sufficient to fully formalize a taxon without ambiguity. However, in practice, taxa are most often only addressed through their name and their extension, circumscribing them by their components (child-taxa) that are added or excluded following the progress of knowledge and discoveries. Here we show that without modifying its content, moving a taxon in the classification affects fundamentally its definition by intension, while the taxon remains considered the same. During taxonomic revisions, a taxonomic concept is not only extended or restricted according to its components, but it can be definitively modified when its contextualization in a classification changes. Because of the recursive property of the classification, defining a taxon by intension is equivalent to addressing its classification, and the taxon is necessarily contextualized. Accordingly, a taxon is therefore only fully defined as a triplet, documenting at the same time its name, its content and its classification, each issue varying independently from each other. If one wants to correctly report or aggregate taxonomic knowledge in taxonomic databases, managing these three issues independently is therefore necessary to assure the relational integrity in the database. Particularly, all aspects managing the taxon contextualization (e.g. its classification) and its eventual changes should be included in taxonomic databases and some recommendations are provided. As discussed, consequences in the taxonomic treatment of the related data that follows the taxa (not the name!) remain underestimated and still need to be better understood and formalized. As complex human concepts, taxa modelization for the digital world remains a real challenge and shows that taxonomy is a much more complex science than usually expected.